2006
DOI: 10.1161/01.atv.0000229243.49320.c9
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic Murine Endothelial Progenitor Cells Are Derived From a Myeloid Bone Marrow Fraction and Can Be Identified by Endothelial NO Synthase Expression

Abstract: Objective-Endothelial progenitor cells (EPCs) contribute to postnatal neovascularization and are therefore of great interest for autologous cell therapies to treat ischemic vascular disease. However, the origin and functional properties of these EPCs are still in debate. Methods and Results-Here, ex vivo expanded murine EPCs were characterized in terms of phenotype, lineage potential, differentiation from bone marrow (BM) precursors, and their functional properties using endothelial NO synthase (eNOS)-green fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 50 publications
(65 reference statements)
2
62
0
1
Order By: Relevance
“…In addition, no substantial differences were found in absolute numbers of T cells, B cells, natural killer cells, plasmacytoid dendritic cells, neutrophils, or eosinophils. Because circulating myeloid cells are known to display proangiogenic properties 36 and we previously demonstrated that proangiogenic cells could be cultured from a BMderived immature, CD31 + /Ly6C hi myeloid progenitor cell fraction, 37 the monocytic cells were further subdivided into Ly6C hi , Ly6C med , and Ly6C lo fractions. Again, however, no significant differences could be observed between the experimental groups.…”
Section: Lv-126 Mice Display Increased Hematopoietic Stem Cell and Prmentioning
confidence: 99%
“…In addition, no substantial differences were found in absolute numbers of T cells, B cells, natural killer cells, plasmacytoid dendritic cells, neutrophils, or eosinophils. Because circulating myeloid cells are known to display proangiogenic properties 36 and we previously demonstrated that proangiogenic cells could be cultured from a BMderived immature, CD31 + /Ly6C hi myeloid progenitor cell fraction, 37 the monocytic cells were further subdivided into Ly6C hi , Ly6C med , and Ly6C lo fractions. Again, however, no significant differences could be observed between the experimental groups.…”
Section: Lv-126 Mice Display Increased Hematopoietic Stem Cell and Prmentioning
confidence: 99%
“…An in vitro angiogenesis assay was performed as previously described (Loomans et al 2006). EPCs pretreated with LY294002 or L-NAME for 1 h, were treated with PIN (10-20 mg/L) and digested with 0.25 % trypsin.…”
Section: Formation Of Tubes In Vitromentioning
confidence: 99%
“…We previously provided evidence that early outgrowth EPC, Mph, and DC may share a common myeloid progenitor pool in the BM (25). Therefore, the potential of the BM cells to differentiate into F480 + Mph and CD11c + DC in M-CSF-and GM-CSF-stimulated cultures, respectively, was assessed in parallel to the EPC cultures.…”
Section: Hyperglycemia Differentially Alters the Potential Of Bm Cellmentioning
confidence: 99%
“…CD14 + cells have long been known to play a critical, paracrine role in neovascularization (22), and it is highly likely that "early outgrowth" EPC derived from CD14 + cells directly reflect the proangiogenic phenotype of monocytes that have entered ischemic tissue that is rich in vascular endothelial growth factor (23,24). We have previously demonstrated that in mouse BM these angiogenic EPC develop from an immature, CD31 + /Ly-6C + myeloid progenitor fraction (25). Given the proper differentiation factors, however, these BM precursor pools also give rise to important effector cells of the innate immune system such as macrophages (Mph) and dendritic cells (DC) (26,27), suggesting a common myeloid progenitor pool for EPC, Mph, granulocytes, monocytes, and DC.…”
Section: Introductionmentioning
confidence: 99%